A Place for Technology in Parent Education: An Exploratory Study of Parent Perceptions. Issue 8 (17th November 2017) - Stanley, Jennie Lynn; Vaterlaus, J. Mitchell; Tulane, Sarah; Beckert, Troy E.
ABSTRACT: The current study sought to identify what parents would perceive to be helpful in terms of including technology topics in parent education programs, rather than assuming what would be best for parents. Parents were recruited for participation from a western state in the United States between 2012 and 2013. A qualitative approach was used to analyze parental responses ( N  = 168) regarding what topics/areas would be beneficial if they attended an educational offering relating to teens and technology. Parents indicated they wanted specific direction and skills relating to the practice of implementing parental mediation, and information about staying current with the technology trends. Other findings focused on the difficulty of getting parents to commit to such education.